(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Sudden cardiac death (SCD) is a major cause of mortality secondary to coronary artery disease (CAD). Though it is one of the commonest causes of natural death but is contested too often. SCD of someone under the suspicion of violence means differently to different persons. Larger perception of the death due to suspected or known violence ignites an intolerance debate “Pro SCD versus Anti SCD”. Controversy into the cause of death ultimately ends but acrimony lingers. Aim: To study autopsy physician’s limitation, the role of general presumptions and biases in meeting with the expectation and demand of unwavering and unequivocal medical opinions. It is also to know & identify how embarrassments took place, who embarrassed and who tried to hit the clinician. Material & method: A total of 13 SCD cases retrospectively reviewed and these cases were reported between 2009 to 2018. These cases landed into controversy due to the conflicting cause of death and missing injury. Dispute revolved around linking or delinking the injury to SCD. Re-examination was either solicited or ordered for further clarification as autopsy opinions either did not work or worked after rectification. In some cases, the issue over SCD was decided after multiple reviews. In other cases, the dispute over injury related SCD was decided after the trial in the court.